2018
DOI: 10.3390/ijms19051342
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Potential of Sea Cucumbers

Abstract: This review presents a detailed analysis of published research data focused on the pharmacological activity exerted by biologically active compounds isolated from sea cucumbers belonging to the class of Holothuroidea, phylum Echinodermata. The review contains descriptions of the structure, physico-chemical properties and pharmacological effects of these active substances. Particular attention is given to compounds with anticoagulant, antithrombotic, antioxidant, anticancer, anti-infectious, immune-stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 152 publications
5
103
0
3
Order By: Relevance
“…On the other hand, the data reported here strongly suggest that such water-soluble constituent(s) is/are resistant to lyophilization, resuspension, and freeze-thawing cycles, and must supposedly have a MW < 10 kDa since the biological activity is retained and ameliorated after filtration of the crude extract. In light of the literature data, sea cucumber-derived anti-cancer molecules that exhibit this size fall into the categories of triterpenes, glycosaminoglycans, and peptides [8,50]. At present, we cannot exclude the existence of potential synergic activities, as reported by Guo et al [51].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, the data reported here strongly suggest that such water-soluble constituent(s) is/are resistant to lyophilization, resuspension, and freeze-thawing cycles, and must supposedly have a MW < 10 kDa since the biological activity is retained and ameliorated after filtration of the crude extract. In light of the literature data, sea cucumber-derived anti-cancer molecules that exhibit this size fall into the categories of triterpenes, glycosaminoglycans, and peptides [8,50]. At present, we cannot exclude the existence of potential synergic activities, as reported by Guo et al [51].…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, growing evidence has demonstrated that the extracts of different holothurian species are endowed with several varied biological and pharmacological properties, spanning from anti-angiogenic and anticancer to antimicrobial and anticoagulant activities (e.g., [1,6,7]). Such effects have been ascribed to the presence of numerous bioactive compounds among which the most characterized to date are the triterpene glycosides saponins, accounting for more than 300 different molecules, along with components of various macromolecular nature, such as glycosaminoglycans, phenolics, and peptides [8].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, although the potential anti-cancer compounds obtained from echinoderms have been widely illustrated in the literature [49], the contribution of sea urchins to this field of research is still very limited and is represented only by a few pilot studies previously published and which focused on steroidal and polysaccharidic constituents [4,50,51]. Here, we have demonstrated the cytotoxicity of extracts from A. lixula's cell-free CF towards TNBC cells in vitro.…”
Section: Discussionmentioning
confidence: 68%
“…Having high nutritional and medicinal qualities, sea cucumber has been drawn notable attention [9]. There is culminating evidence that polysaccharides from sea cucumber have an effective anti-diabetic activity [16,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, due to the huge species biodiversity and extremely harsh living environment, marine organisms have been found to have biologically active agents which show antidiabetic effects, and the sea cucumber is one of the most widely used marine traditional medicines in Asia [8,9]. Sea cucumbers are echinoderms from the class Holothuroidea with a wide spectrum of biological and pharmacological activities, such as anti-cancer [10], anticoagulant [11], antifungal [12], anti-hypertension [13], antioxidant [14], anti-inflammatory [15], anti-diabetic [16] and antiviral [17] activities.…”
Section: Introductionmentioning
confidence: 99%